The Relationship between Self-Esteem and Religiosity the Initiation of Premarital Sex Among Teenagers in Lasolo Islands, North Konawe Regency - Suryani, Rahma; Nova Noviyanti Rachman, Wa Ode; Asbath, Asbath (Magister Kesehatan Universitas Mandala Waluya, 2025)
Introduction: Adolescence is a developmental phase between childhood and adulthood. Data from the North Konawe District Health Service for 2023 shows that 17.3% of teenagers have had petting, 5.3% have had oral sex, 3.6% have had vaginal sex, 2.5%. Factors that can trigger the initiation of premarital sex include self-esteem, religiosity, the media role of parents and peers. This research aims to determine the relationship between self-esteem and religiosity with the initiation of premarital sex among teenagers in Lasolo Islands, North Konawe Regency. Method: This type of research is quantitative research, cross sectional study design which was carried out from April 18 to May 18, 2024 at Public Middle School 2 Asera and public senior high school 1 Lasolo Islands. The population of this research was all 137 teenagers from Public Middle School 2 Asera and 121 students from public senior high school 1 Lasolo Islands and a sample of 70 people was obtained using proportional random sampling. Data were collected using a questionnaire and analyzed using the chi-square test, closeness and binary longistic regression. Result: The results of the Chi-Square test on self-esteem obtained ap value of 0.000 and φ (0.505) and religiosity p value 0.004 < α (0.05). The results of the multiple logistic regression test, the smallest significant value is self-esteem with a significant value of 0.000 and Wald 7.682. Conclusion: There is a moderate relationship between self-esteem and weak religious relationships with the initiation of premarital sex among teenagers in Lasolo Islands, North Konawe Regency.